Prevalence and clinical association of MET gene overexpression and amplification in patients with NSCLC: results from the European Thoracic Oncology Platform (ETOP) Lungscape project - Bubendorf, Lukas; Warth, Arne (Lung cancer, 2017)
Introduction In a well-defined NSCLC cohort of the ETOP Lungscape program, we explored the epidemiology of IHC MET overexpression and amplification, their inter-correlation, and their association to outcome. Methods Resected NSCLC were assessed for MET gene copy number (GCN) and expression using silver in-situ hybridization (SISH) and immunohistochemistry (IHC) on TMAs in a multicenter setting. MET amplification was defined as MET/centromere ratio≥2 (with average MET GCN≥4), high MET GCN as CGN≥5 and MET IHC+ as ≥2+ intensity in ≥50% of tumor cells. A total of 182 MET IHC+ and EGFR/KRAS WT tumors were analyzed for METex14 skipping mutation. Results MET IHC+ was found in 23.8% of 2432 patients, significantly associated with female gender, small tumor size, and adenocarcinoma histology. We observed a high inter-laboratory variability in IHC and SISH analysis. MET amplification prevailed in 4.6% and MET GCN≥5 in 4.1% of 1572 patients. MET amplification and MET GCN≥5 were not significantly associated with any tumor characteristics or stage. Both were significantly associated with IHC MET positivity (p<0.001). METex14 skipping mutation prevailed in 5 of 182 (2.7%) MET IHC+ WT EGFR/KRAS NSCLC, 4 of which within the 88 adenocarcinomas (4.5%). No association of IHC MET overexpression, SISH MET amplification or high MET GCN was found with OS, RFS or TTR. Conclusion MET overexpression is found in 23.8% of surgically resected NSCLC. MET amplification prevails in 4.6% and is associated with MET overexpression. Both have no influence on prognosis. The large inter-laboratory variability in IHC highlights the challenge of MET IHC analysis in routine practice.